Statewide Community-based Health Promotion: A North Carolina Model to Build Local Capacity for Chronic Disease Prevention - Marcus Plescia, MD, MPH; Suzanna Young, RD, MPH; Rosemary L. Ritzman, PhD, MSN (Centers for Disease Control and Prevention, 2005)
Background Public health faces major challenges to building state and local infrastructure with the capacity to address the underlying causes of chronic disease. We describe a structured statewide approach to providing technical assistance for local communities to support and develop health promotion capacity. Context Over the last two decades, the North Carolina Statewide Health Promotion program has supported local approaches to the prevention and control of chronic disease. In 1999, a major change in the program required local health departments to focus on policy-change and environmental-change strategies for addressing three major risk factors: physical inactivity, poor diet, and tobacco use. Methods State program consultants provided technical assistance and training opportunities to local programs on effective policy-change and environmental-change strategies and interventions, based on needs defined by a statewide monitoring and evaluation system. Consequences The percentage of health departments in North Carolina with interventions addressing at least one of three targeted risk factors in 2004 approached 100%; in 2001, this percentage was 62%. Additionally, between 2001 and 2004, the number of health departments reporting policy or environmental outcomes related to these risk factors almost doubled.